Polybioside, a Neuroactive Compound from the Venom of the Social Wasp Polybia paulista - Saidemberg, Daniel M. [UNESP]; da Silva-Filho, Luiz C. [UNESP]; Cesar Tognoli, Lilian M. M. [UNESP]; Tormena, Claudio F.; Palma, Mario Sergio [UNESP] (Amer Chemical Soc, 2010)
Polybioside (1) was isolated from the venom of the social wasp Polybia paulista, and its structure was assigned as 3,4,5-trihydroxy-6-(hydroxymethyl)tetrahydro-2H-pyran-2-yl 3-(1H-imidazol-4-yl)propanimidate by NMR and MS protocols. The application of polybioside in rat brain, followed by the detection of c-Fos protein expression in some brain regions, indicated the compound is neuroactive in a number of brain areas. Polybioside causes convulsions in rats, even when peripherally applied.